Advances in Heat Exchangers - Castro Gómez, Laura; Manuel Velázquez Flores, Víctor (IntechOpen, 2019)
Heat exchangers are important devices for engineering, research, and industry. Because of this, any improvement helps to optimize the whole process. Opportunity areas may be found in design, materials, or working fluids. In this sense, the present book compiles some advances in the matter of design (three chapters) and working fluids (one chapter). An introductory chapter also is presented.